The problems of surgical training in gynaecologic oncology - Burger, CW (2008)
During the late 60s and early 70s it was recognised that the surgical training for residents in Obstetrics and Gynaecology was inadequate to comprehensively acquire the surgical skills necessary in managing women with gynaecologic cancers. Gynaecologic Oncology (Gynae-Oncology) has three important goals: 1) to maintain the highest standards for patients with gynaecologic cancer, 2) to provide the trainee with clinical skills and structural clinical research after his/her surgical completion, and 3) to acknowledge clinical training centers for the trainees in Gynae-Oncology. For women trainees careful family planning, good communication, flexibility from the program director and faculty, support from co-workers, and, most important, participation and support from the spouse of the trainee are the ingredients of successful childbearing and family care during training programs. These problems have to be faced and dealt with before they become insurmountable problems. International standards are needed for training programs of trainees in Gynae-Oncology, with special emphasis on surgical skills.